If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -7) = 6x + -12 Reorder the terms: 3(-7 + 5x) = 6x + -12 (-7 * 3 + 5x * 3) = 6x + -12 (-21 + 15x) = 6x + -12 Reorder the terms: -21 + 15x = -12 + 6x Solving -21 + 15x = -12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -21 + 15x + -6x = -12 + 6x + -6x Combine like terms: 15x + -6x = 9x -21 + 9x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -21 + 9x = -12 + 0 -21 + 9x = -12 Add '21' to each side of the equation. -21 + 21 + 9x = -12 + 21 Combine like terms: -21 + 21 = 0 0 + 9x = -12 + 21 9x = -12 + 21 Combine like terms: -12 + 21 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| 4log(X)=7 | | 15.5=16-x/12 | | 2x+3y=-45 | | 3+4(x+4)=3(x-4) | | -x-4-4x=x-46 | | (x-2)/4=2 | | -15=3b+(-6) | | 4logx=7 | | 16=18-x/3 | | 2(x-2)+x=11 | | 8r^2-72r+64=0 | | 7x+2=-6x-154 | | 10+3b-5=12+b-3b | | 2x-3y+2z=-5 | | 0=-16x^2-16x+160 | | x-291=-8x-3 | | 17x-23=8y-12 | | -7=a/-19 | | -5/y=-10 | | 3d+8=11 | | 39x+19=100 | | -22=a/6 | | G(-1)=xsquared+1 | | 0=-16x^2+160x+32 | | 4/9×1/8 | | W=G+Grt | | M/23=-16 | | -11.25t+5=14 | | -4b+(-9k)-6-3b+12= | | M/18=-17 | | 3g+9+2g+5=50 | | 2+5x-8=2x-4+x |